Legitimacy In European Nature Conservation Policy Case Studies In Multilevel Governance - Keulartz, Jozef; Leistra, Gilbert; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
This volume focuses on the issue of legitimacy in the context of European nature conservation policy. It provides insights in the way in which democratic legitimacy is being 'produced' at different levels of governance. Building forth upon recent developments in democracy theory that have identified multiple forms of legitimacy, the volume observes a EU-wide shift from output legitimacy to input and throughput legitimacy. Top down policy making is increasingly meeting local resistance. As a result, the importance for policy makers of enhancing the democratic legitimacy of their policy plans has increased. The popularity of deliberative decision-making procedures can be seen as a procedural answer to this state of affairs. For this volume scholars from within the EU were invited to reflect upon the question whether similar developments are taking place in the context with which they are most familiar. Do they perceive a delegitimation of top down policy making and hence an increasing emphasis on procedural legitimacy in processes of nature conservation policy implementation? Which model of democratic decision-making is most helpful to solve the issue of legitimacy in the field of nature conservation policy? How important are national traditions and institutions? What are the tradeoffs between the different types of legitimacy? Nine case studies are presented: two case studies on protected species (geese in the Netherlands, and the great cormorant in Denmark, France and Italy), four case studies that zoom in on specific protected areas (in Spain, Finland, Poland and the UK), and three case studies with a focus on the implementation of Natura 2000 at the country level (Belgium, France and Germany). These case studies are followed by extensive comments.
European Nature Conservation Policy Making -- Protected Species -- Wintering Geese in the Netherlands -- Vindicating Arrogant Ecologists -- Legitimacy of Species Management -- Animal Governance: The Cormorant Case -- Protected Areas -- Legitimacy Problems in Spanish Nature Policy -- How to Deal with Legitimacy in Nature Conservation Policy? -- Resistance to Top-Down Conservation Policy and the Search for New Participatory Models -- Visions and Scales of Nature and Society in Nature Management -- Creation of a Bottom-Up Nature Conservation Policy in Poland -- Nature Conservation in Poland and the Netherlands -- Conservation in Context: A View from below -- Towards Governance and Procedural Legitimacy? -- Countries -- Endangered Legitimacy -- Nature Policy in Flanders -- Between European Injunction and Local Consultation -- The Local Implementation of Nature Policy -- Legitimacy of Biodiversity Policies in a Multi-level Setting -- Are Conflicts of Nature Distributive Conflicts? -- Conclusions -- European Union Environmental Policy and Natura 2000.
Keywords: ENVIRONMENTAL SCIENCES; POLITICAL SCIENCE -- PHILOSOPHY; REGIONAL PLANNING; BIODIVERSITY; NATURE CONSERVATION; POLITICAL SCIENCE; ENVIRONMENT; NATURE CONSERVATION; POLITICAL SCIENCE; POLITICAL PHILOSOPHY; LANDSCAPE/REGIONAL AND URBAN PLANNING; BIODIVERSITY